Politik legislasi Menentukan DeMokrasi (analisis Putusan no. 15/Puu-iX/2011) - Wahid, Abdul (Jurnal Konstitusi, 2012)
Not  all  juridical  products  are  along    with  the  society’s  aspiration.  There     are some of the juridical products assessed as against the democracy  enforcement by  the  society.  The  verdict  number  15/PUU-IX/2011  given  by  the Constitutional Court is a kind of correction to the performance of the  lawmakers (UU) if the law they produce are considered contra-democracy. Besides,  the  verdict  of  the  Constitutional  Court  to  some  of  the  articles  in  the  Law  No.  2  Year  2011  actually  might  be  read  as  a  warning  from    the Constitutional Court to the lawmakers, especially those regulating  the  problem of  political  parties  so  that  their  performance  could  be  maximized  and  transparent,  and  consider  egalitarianism  in  the  future.